Passenger Service - Solano Martínez, Hugo (2007)
This paper shows the simulation of the passenger service system of an airline at the Jorge Chávez International Airport for a specific service shift. This is achieved by building a model based on stochastic process theory and stochastic process theory and reliability theory. In addition, using said offers as selected application. This distribution is very important for the company because it allows it to optimize its passenger service system, with more staff during the minutes when there are more passengers, and less staff otherwise.